Professional service firms as agents of economic globalization: A political perspective. Issue 1 (2nd November 2018) - Boussebaa, Mehdi; Faulconbridge, James R
Abstract: In recent decades, numerous professional service firms have gone 'global' in search of new markets and to support clients requiring services across nations. Whilst a lively debate has developed over the organizational implications of this phenomenon, the role of the firms in globalizing the wider world economy has received much less attention. In this paper, we address this imbalance through an inter-disciplinary synthesis of the literature at the intersection of the professions and economic globalization and apply a political perspective to frame our analysis. Our contribution is twofold. First, we argue for a broadening of the research agenda to better elucidate the critical role of professional service firms as agents of economic globalization . This role, we argue, should become a core research theme given the firms are not just businesses offering services across the globe but also active participants in the globalization of the world economy. Secondly, we shed light on and conceptualize the specific power strategies deployed by the firms as part of their role as agents of economic globalization. We develop an integrative framework which, firstly, distinguishes between 'design' and 'implementation' and, secondly, specifies how the firms exert power to their advantage in each of these related areas. This model provides a theoretical scaffolding for understanding how professional service firms shape and indeed become hegemonic agents of economic globalization.